Clinical characteristics and therapeutic direction of HER2 low-expression breast cancer - Zhou, Linlin; Zhang, Yinghui; Zhang, Jiayu; Wang, Hongyu; Zhao, Bozhi; Cai, Yixin; Qu, Yuansong; Li, Xinxin; Zhang, Dongwei (Frontiers in Oncology, 2025)
Human epidermal growth factor receptor 2 (HER2) is one of the oncogenic drivers of breast cancer and is often used as a definitive therapeutic marker for breast cancer. This has led to significant improvements in both targeted therapy and prognosis for HER2-targeted breast cancer. Due to the differences in HER2 gene and protein expression levels, they are clinically classified into HER2 zero-expression breast cancer, low-expression breast cancer and high-expression breast cancer. Among them, HER2 low-expression is considered a special expression state, which is insensitive to conventional anti-HER2 therapy and has a poorer prognosis and thus has received attention from researchers. Some studies demonstrate that patients with HER2 low-expression can benefit from antibody-drug conjugates (ADC). Several studies are currently exploring the efficacy of various ADC drugs in breast cancer with HER2 low-expression, opening up new treatment avenues for patients with HER2 low-expression breast cancer. This review aims to summarize the clinical features of HER2 low-expression breast cancer and the recent advances in its therapeutic agents.